The Effectiveness of Updating Data on Small and Medium Industrial Business Actors in the Industrial Sector at the Cirebon City Cooperatives, Small and Medium Enterprises, Trade and Industry Office - Rizki Anditiana, Agnesa; Aziza Pratiwi, Nabilla; Pangestu Manchini, Puji; Nursahidin; Heryanto, Yanto (Jurnal Polisci, 2024)
The development of Science and Technology (IPTEK) affects various aspects of human life, including in the context of organizations and government agencies. In Cirebon City, the management of Small and Medium Industries (SMEs) by the Trade and Industry Small and Medium Business Cooperative Office faces challenges in updating data that has not been fully computerized. This study uses a descriptive qualitative approach to evaluate the effectiveness of the IKM data update process. The study results show that the number of SMEs is increasing every year, although there are still obstacles, such as incomplete information and manual processes that slow down efficiency. The application of digital technologies, such as applications for data collection and update, is proposed as a solution to improve the efficiency and accuracy of processes. It is hoped that better data updates, facilitated by digital technologies, can significantly support the development of the creative economy of Cirebon City through the identification of more appropriate needs and opportunities, as well as the optimization of government programs in the SME sector.